Numerical simulation of the sensor for toxic nanoparticles based on the heterostructure field effect transistor - V. S. Volcheck; V. R. Stempitsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A significant rise in the mass production of products that contain nanoparticles is of growing concern due to the detection of their toxic effects on living organisms. The standard method for analyzing the toxicity of substances, including nanomaterials, is toxicological testing, which requires the substantial consumption of time and material resources. An alternative approach is to develop models that predict the effect of nanomaterials on biological systems. In both cases, for the detection of nanoparticles an effective electronic complex consisting of a sensor with high sensitivity and a data reception/processing/transmission system is necessary. In recent times, fundamental and applied research activities aimed at the application of heterostructure field-effect transistors – high electron mobility transistors–as a base for such sensors have been undertaken. The purpose of this work is to develop a technique for modeling a sensor for toxic nanoparticles based on the heterostructure field-effect transistor. The object of the research is a gallium nitride high electron mobility transistor device structure. The subject of the research is the electrical characteristics of the transistor obtained in static mode. The calculation results show that the dependence between the concentration of the toxic nanoparticles in the test medium and the polarization charge surface density could serve as a base for modeling the sensor for toxic nanoparticles based on the heterostructure field-effect transistor. The primary advantage of the proposed technique is the use of the scaling parameter intended directly for calibrating the polarization charge density in accordance with the two-dimensional electron gas concentration. The obtained results can be utilized by the electronics industry of the Republic of Belarus for developing the hardware components of gallium nitride high-frequency electronics.